AN ASSESSMENT OF THE POTENTIAL OF PHOTOVOLTAIC LITHIUM SOLAR CELLS FOR ELECTRICITY GENERATION IN KATSINA STATE. - Salisu, Bashir (FUDMA JOURNAL OF SCIENCES, 2020)
A photovoltaic cell is a specialized semiconductor diode that converts visible light into direct current(DC).Some Photovoltaic (PV) cells can also convert Infrared (IR) or ultraviolet (UV) radiation into DC electricity. In this research article a special pyranometer laboratory instrument (containing Prepared sample of Silicon,Si and Lithium,Li on a sample holder) was used to measure/assess the Solar radiation in katsina state and determine the best/highest potential element between Si and Li in respect of energy production.The samples ware prepared in form of a thin-film using synthesis and characterization. It was stated in the literature that silicon has been used industrially over decades in manufacturing photovoltaic cells, but it has a drawback of degrading over time, hence the idea of introducing another element (Li) to replaced it.The results of this research were  obtained from three(3) areas of katsina state:viz Daura, Funtua and Katsina.The result shows that: from Funtua loction Lithium thin-film absorbed an extra energy of (4.6 kw/m2) over Silicon, likewise in Daura and Katsina, there is a differences of (4.6 and 5.0) kw/m2 which lithium have over silicon respectively. This gives Lithium priority to be used industrially over silicon.Also this result qulifies Katsina state to be a very good location for solar power plant, since the visible light intesity is in good agreement with Standard Surface Solar Irradiation (SSI).
Keywords: photovoltaic, pyranometer, lithium/silicon,solar thin-film,electricity